Pengaruh Direct Route terhadap Beban Kerja Pemandu Lalu Lintas Udara di Perum LPPNPI Cabang Pembantu Pangkalan Bun - Octaviano, Muhammad Arbi; Sadiatmi, Rini; Widyasari, Destyana (SKY EAST: Education of Aviation Science and Technology, 2023)
This study aims to determine how much influence the direct route has on the workload of air traffic guides at Perum LPPNPI Pangkalan Bun Sub Branch.The research was conducted at the Aerodrome Control Tower Unit and Approach Control Unit at Perum LPPNPI Pangkalan Bun Sub-Branch, Central Kalimantan from April to July 2020. The research method used is quantitative research, where direct route is variable x and the workload of air traffic guides. as variable y. The data collection technique was by distributing questionnaires to 15 respondents consisting of all air traffic control personnel at Perum LPPNPI Pangkalan Bun Sub-Branch. The data analysis technique used is tabulating the x and y variables from the obtained questionnaire, followed by the correlation coefficient test and determination. From the calculation results in the discussion of the final project, it is found that there is a strong enough relationship between the effect of direct route on air traffic guidance workload with a correlation coefficient (r) of 0.734 and a coefficient of determination (r2) 54%, meaning that the effect of direct route on the load Air traffic control work at Perum LPPNPI Pangkalan Bun Sub Branch is 54% and the rest is determined by other factors.